Evaluation of Land Redistribution Implementation in Agrarian Reform Program: Legal and Social Perspectives - Novianti, Leny (Jurnal Ilmiah Teunuleh, 2024)
The agrarian reform program in Indonesia aims to realize justice in the control, ownership, use, and utilization of land through land redistribution to marginalized communities. However, its implementation is still faced with various structural and cultural obstacles. This study aims to evaluate the implementation of land redistribution in the agrarian reform program from a legal and social perspective. The method used is descriptive qualitative approach with data collection through literature study, documentation, and policy analysis. The results showed that legally, this program experienced obstacles in the form of overlapping regulations, weak legal certainty, and low coordination between institutions. From the social side, challenges arise in the form of capital owner resistance, lack of community participation, and unpreparedness of local institutions in supporting program implementation. Therefore, the success of land redistribution requires regulatory harmonization, institutional strengthening, and inclusive participatory mechanisms. This evaluation provides important recommendations for policy makers so that agrarian reform does not only become a formality agenda, but is able to bring substantive agrarian justice.